Inhibition of Non-Small Cell Lung Cancer Cells by Oxy210, an Oxysterol-Derivative that Antagonizes TGFβ and Hedgehog Signaling - Frank Stappenbeck; Feng Wang; Liu-Ya Tang; Ying E. Zhang; Farhad Parhami (Cells, 2019)
Non-Small Cell Lung Cancer (NSCLC) is a common malignancy and leading cause of death by cancer. Metastasis and drug resistance are serious clinical problems encountered in NSCLC therapy. Aberrant activation of the Transforming Growth Factor beta (TGFβ) and Hedgehog (Hh) signal transduction cascades often associate with poor prognosis and aggressive disease progression in NSCLC, as these signals can drive cell proliferation, angiogenesis, metastasis, immune evasion and emergence of drug resistance. Therefore, simultaneous inhibition of TGFβ and Hh signaling, by a single agent, or in combination with other drugs, could yield therapeutic benefits in NSCLC and other cancers. In the current study, we report on the biological and pharmacological evaluation of Oxy210, an oxysterol-based dual inhibitor of TGFβ and Hh signaling. In NSCLC cells, Oxy210 inhibits proliferation, epithelial-mesenchymal transition (EMT) and invasive activity. Combining Oxy210 with Carboplatin (CP) increases the anti-proliferative response to CP and inhibits TGFβ-induced resistance to CP in A549 NSCLC cells. In addition, Oxy210 displays encouraging drug-like properties, including chemical scalability, metabolic stability and oral bioavailability in mice. Unlike other known inhibitors, Oxy210 antagonizes TGFβ and Hh signaling independently of TGFβ receptor kinase inhibition and downstream of Smoothened, respectively.